Temne Dream Culture and Charismatic Churches in Sierra Leone: Probing the Limits of Contextualization - Bangura, Joseph Bosco (Evangelical review of theology, 2022)
Many emphasize that Christian ministries in Africa need to engage meaningfully with Africans' sensitivity to the spirit world. But that engagement also presents risks of syncretism or departing from biblical truth. This case study, full of historical detail and biblical insight, examines how some Charismatic ministries in Sierra Leone are accommodating traditional views of dreams, along with the resulting opportunities and pitfalls.